2020
DOI: 10.1186/s40478-020-01019-z
|View full text |Cite
|
Sign up to set email alerts
|

Regional correlation of biochemical measures of amyloid and tau phosphorylation in the brain

Abstract: Alzheimer's disease (AD) neuropathologic change is characterized by amyloid plaques and neurofibrillary tangles (NFTs) that consist of aggregated amyloid beta (Abeta) and hyperphosphorylated tau proteins (p-tau), respectively. Although the global relationship between Abeta and p-tau has been studied for decades, it is still unclear whether a regional correlation exists between Abeta and p-tau in the human brain. Recent studies in cerebrospinal fluid (CSF) have suggested that tau phosphorylation at specific sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 34 publications
3
40
0
Order By: Relevance
“…It is important to note that a fourth phosphorylation site in tau, pS208, may also be recognized by the AT8 antibody (Malia et al, 2016 ). pS208 has been much less studied than the other sites of this epitope, but recent mass spectrometry articles have found evidence of phosphorylation at this site in AD (Barthélemy et al, 2019 ; Horie et al, 2020 ). Soluble, but not insoluble tau purified from AD brains was phosphorylated at S208, although to a lesser extent than S202 or T205 (Horie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that a fourth phosphorylation site in tau, pS208, may also be recognized by the AT8 antibody (Malia et al, 2016 ). pS208 has been much less studied than the other sites of this epitope, but recent mass spectrometry articles have found evidence of phosphorylation at this site in AD (Barthélemy et al, 2019 ; Horie et al, 2020 ). Soluble, but not insoluble tau purified from AD brains was phosphorylated at S208, although to a lesser extent than S202 or T205 (Horie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…pS208 has been much less studied than the other sites of this epitope, but recent mass spectrometry articles have found evidence of phosphorylation at this site in AD (Barthélemy et al, 2019 ; Horie et al, 2020 ). Soluble, but not insoluble tau purified from AD brains was phosphorylated at S208, although to a lesser extent than S202 or T205 (Horie et al, 2020 ). Similar to pT205, pS208 could not be identified in soluble tau from control brain tissues, but low levels were detected in control CSF (Barthélemy et al, 2019 ; Horie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that almost all 231Thr residues are phosphorylated. Recently, phosphorylated tau profiles in soluble brain fractions in AD have been reported (Dujardin et al, 2020;Horie et al, 2020). In one report, Thr111, Ser113, Thr153, Thr181, Ser199, Ser202, Thr205, The217, Thr231, Ser262, and Ser396, and in the other, Thr181, Ser198, Ser199, Ser202, Thr217, Thr231, Ser262, Ser400, Thr403, Ser404 were phosphorylated, but in our analysis, all of these sites except Thr153 and Ser205 were phosphorylated (Table 2 and Supplementary Table 3).…”
Section: Other Characteristic Ptmsmentioning
confidence: 99%
“…Previously known AD markers including Tau and amyloid-beta peptides have been identified across multiple mass-spectrometry-based proteomics studies and have been successfully developed into targeted assays for quantitation [ 44 , 45 , 46 , 47 ]. Multiple studies by Barthelemey et al and groups have studied tau phosphorylation in CSF, brain, and plasma and reported an association between site-specific changes in tau phosphorylation and evolution of stages of dominantly inherited Alzheimer’s disease [ 48 , 49 , 50 ]. Another large-scale analysis of the CSF from AD patients has identified a consistent glycolytic signature [ 51 ].…”
Section: Proteomics Studies In Ad Pathogenesis and Biomarker Discomentioning
confidence: 99%